Structural Changes in Alveolar Walls in Chronic Smokers and Serum Surfactant Protein A Levels - Saira Aslam, Ahmad Farzad Qureshi, Nadia Haq, Kanwal Khalid, Muhammad Amjad Bari, Kalsoom Akhter, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
This prospective cross-sectional study examined structural alterations of alveolar walls and serumsurfactant protein A (SP-A) levels in chronic cigarette smokers compared with matched nonsmoking controls. The objective was to quantify alveolar septal thickening, emphysematous changes and correlate these with circulating